An artist'a adventures sketches note 60 days in Europe - Fai Zakaria (Institut Terjemahan & Buku Malaysia, 2015)
My Ayah is my strength. He is also my confident, the one who is always there for me and the one who i have faith in. He was the first person I told that his only daughter would be away during the Eid Ul-Fitr celebrations, representing Malaysia at an exhibition in Vienna. Initially, his face lit up, but quickly that expression changed when he weighed up the work and preparation it would take. Being Asian especially a Malay-born lady, it is not common for a single female to travel alone to a foreign land, let alone for sixty days. There were friends and acquitances who were against the idea of me travelling to Europe alone, citing security as thier main concern. "It's not our culture. What happens if..." was the question that i was bombarded with. All the negatively did actually give me unwarranted concern. Eventually, I gathered that when you travel you observe the beauty of the place, not the ugliness, thus my ticket was booked. Ayah had his concerns too, so did I, but Ayah, despite his reservations, assured me that being aware of my fear was a good move. Overcoming it its the mark of a succesful person. He taught me that strenght from overcoming obstacles is the only strenght that can overcome adversity. When there is a will, there will always be a way. This book is living proof. It was not always a bed of roses but it was an experience that made me the person I wanted to become. I always believe "Let Go and Let God." Allah knows best